ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI OMZET UMK KULINER DI KOTA MALANG - Putri, Chika Avianda; Muhammad Dandy Alif Wildana (Contemporary Studies in Economic, Finance and Banking, 2024)
Micro, Small and Medium Enterprises (MSMEs) have contributed greatly to the Indonesian economy through GDP and employment. The development of MSMEs is caused by supporting factors, such as capital, labor, length of business, working hours, and technology. Quick Response Code Indonesian Standard (QRIS) is a new payment instrument issued by BI to support a more efficient non-cash payment system. This study aims to determine the effect of QRIS, capital, labor, length of business, and working hours on the turnover of culinary MSEs in Malang City. This study uses primary data in the form of questionnaires distributed directly to 75 respondents. The method used in this research is multiple linear regression to test the influence between variables. The results of this study indicate that the effect of QRIS use, length of business, and working hours has no significant effect on MSE turnover in Malang City, while capital and labor have a significant effect on MSE turnover in Malang City. However, all independent variables jointly affect the dependent variable of MSE turnover in Malang City.